The English Football Association Charter for Quality: the development of junior and youth grassroots football in England. (1st November 2016) - Howie, Les; Allison, Wayne
Abstract : In this article, we provide a practitioner's account of the work undertaken by the English football association (FA) in the field of junior and youth grassroots football over the past two decades. We cover The FA's main achievements and challenges in implementing strategies and changes in the delivery and provision of grassroots football. In doing so, we draw upon some of the research The FA has commissioned and undertaken to inform the developments that have been and continue to be made. It is rare for organizations such as The FA to communicate their work and contextualize the challenges and innovations within which this work takes place. As such, we hope this contribution will inform the reader of the past and future innovations that are central to sustaining and developing the grassroots game.